Physiological potential of eggplant seeds - Lopes,Magnólia de Mendonça (2013)
The use and efficiency of vigor tests depend on the plant species and the development and, or adjustment of methodology, to obtain efficient procedures for evaluating seed physiological potential. The objective of this study was to compare different methods for evaluating the physiological potential of eggplant seeds (Solanum melongena L). Six seed lots of the "Comprida Roxa" cultivar were submitted to the following tests: germination, first count germination, seedling emergence, controlled deterioration (18, 21 and 24% for 24 and 48 hours at 45 °C), accelerated ageing (AA) and saturated salt accelerated ageing (both at 41 and 45 °C for 24, 48 and 72 hours) and electrical conductivity (25 seeds, 50 and 75 mL of water for 1, 2, 4, 8, 12, 16 and 24 hours of imbibition at 25 °C). The first count test provided preliminary information on seed germination and the other tests, in general, gave similar results for seedling emergence. It was concluded that the physiological potential of eggplant seeds can be evaluated using AA for 48 h/41 °C and controlled deterioration at 24% moisture content/ 24 h/45 °C. The best conditions for the electrical conductivity test on eggplant seed are using 25 seeds in 50mL of water for four hours at 25 ºC.